Marcadores de DNA microssatélites e estimativa da variabilidade genética da Piramutaba (Brachyplatystoma vaillantii) no Rio Madeira-AM no contexto da construção de hidrelétrica - Carvalho, Katia Cilene Gomes de (2015)
The Madeira River is the second longest river in the Amazon basin, with 3.200km from its source to its mouth in the Amazon river. The system contained 19 rapids, which Jirau, Teotonio and Santo Antonio were the main due to its length demarcating environments and navigation. With the construction of hydroelectric dams in Jirau on ilha do Padre and of Santo Antonio on Santo Antonio Waterfalls, these were extinguished and the river dynamics has changed including the potential distribution of the species. The Madeira River is considered nursery for some species of migratory catfish, as Brachyplatystoma vaillantii, which is able to migrate about 4500 kilometers in search of distinct areas for reproduction, feeding and breeding being highly exploited and currently is in growth overfishing. The genetic variability is an essential component for the survival and adaptation of a species. As piramutaba is one of the most captured fish and exploited in the Amazon, the knowledge of their genetic variability is of great importance for the conservation of its stock. In this context, this work developed microsatellite molecular markers for Brachyplatystoma vaillantii, applying them in the study of genetic variability along the Madeira River, considering the waterfalls of Santo Antonio and Teotônio as barriers to gene flow of this species. This dissertation is divided into two chapters in scientific articles format. In Chapter I 22 microsatellite loci were developed and tested its amplification in the other species of the genus Brachyplatystoma. There were no monomorphic loci among 37 individuals B.vaillantii. The number of alleles per locus ranged from 2 to 14 and the values in the observed and expected heterozygosity ranged from 0.111 to 0.966 and 0.106 to 0.929 respectively. Three loci showed a significant deviation from HardyWeinberg equilibrium and linkage disequilibrium was detected between Bva05 and Bva06 loci. A successful cross-amplification was made of these molecular markers for other species of Brachyplatystoma, an individual Phractocephalus hemiliopterus and Pseudoplatystoma punctifer. In the chapter II the spatial genetic variability was estimated in 7 localities of the Madeira River applying in 10 polymorphic loci, of which 121 alleles were obtained with an average of 12.10, range 4-18 alleles per locus and size between 164-356 base pairs. The average observed heterozygosity and expected heterozygosity was from 0.768 to 0.833, respectively. The temporal genetic variability was estimated among four annual periods using 10 polymorphic loci, which were obtained 118 alleles, with an average of 11.80, range 4-17 alleles per locus and size between 191-346 base pairs. The observed heterozygosity was 0.829 and the expected heterozygosity was 0.769, showing high variability in both analyzes. Wright's F statistics did not indicate genetic structure between localities (FST = 0.013 to 0.007 for spatial analysis and spatial analysis). The genetic distance between the seven localities ranged from 0 to 0.032, and the analysis of temporal genetic variability from 0 to 0.014 indicating highly homogeneous distribution. The Bayesian analysis using the program STRUCTURE presented one cluster (K = 1), indicating lack of structuring. This data may be showing a historical status of the species on the Madeira River that may help in the conservation and management of Brachyplatystoma vaillantii. Keywords: Microsatellite Markers. Brachyplatystoma vaillantii. Genetic Variability. Santo Antônio Waterfall. TeotônioWaterfall.